Production, purification and characterization of recombinant human R-spondin1 (RSPO1) protein stably expressed in human HEK293 cells - Levin, Gabriel (BMC Biotechnol, 2020)
BACKGROUND: The R-Spondin proteins comprise a family of secreted proteins, known for their important roles in cell proliferation, differentiation and death, by inducing the Wnt pathway. Several studies have demonstrated the importance of RSPOs in regulation of a number of tissue-specific processes, namely: bone formation, skeletal muscle tissue development, proliferation of pancreatic β-cells and intestinal stem cells and even cancer. RSPO1 stands out among RSPOs molecules with respect to its potential therapeutic use, especially in the Regenerative Medicine field, due to its mitogenic activity in stem cells. Here, we generated a recombinant human RSPO1 (rhRSPO1) using the HEK293 cell line, obtaining a purified, characterized and biologically active protein product to be used in Cell Therapy. The hRSPO1 coding sequence was synthesized and subcloned into a mammalian cell expression vector. HEK293 cells were stably co-transfected with the recombinant expression vector containing the hRSPO1 coding sequence and a hygromycin resistance plasmid, selected for hygro(r) and subjected to cell clones isolation. RESULTS: rhRSPO1 was obtained, in the absence of serum, from culture supernatants of transfected HEK293 cells and purified using a novel purification strategy, involving two sequential chromatographic steps, namely: heparin affinity chromatography, followed by a molecular exclusion chromatography, designed to yield a high purity product. The purified protein was characterized by Western blotting, mass spectrometry and in vitro (C2C12 cells) and in vivo (BALB/c mice) biological activity assays, confirming the structural integrity and biological efficacy of this human cell expression system. Furthermore, rhRSPO1 glycosylation analysis allowed us to describe, for the first time, the glycan composition of this oligosaccharide chain, confirming the presence of an N-glycosylation in residue Asn137 of the polypeptide chain, as previously described. In addition, this analysis revealing the presence of glycan structures such as terminal sialic acid, N-acetylglucosamine and/or galactose. CONCLUSION: Therefore, a stable platform for the production and purification of recombinant hRSPO1 from HEK293 cells was generated, leading to the production of a purified, fully characterized and biologically active protein product to be applied in Tissue Engineering.